If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12(x+3)+4(4x-3)=3(x-6)+14
We simplify the equation to the form, which is simple to understand
-12(x+3)+4(4x-3)=3(x-6)+14
Reorder the terms in parentheses
+(-12x-36)+4*(4x-3)=3*(x-6)+14
Remove unnecessary parentheses
-12x-36+4+*(+4x-3+)=+3+*(+x-6+)+14
Reorder the terms in parentheses
-12x-36+(+16x-12)=3*(x-6)+14
Remove unnecessary parentheses
-12x-36+16x-12=+3+*(+x-6+)+14
Reorder the terms in parentheses
-12x-36+16x-12=+(+3x-18)+14
Remove unnecessary parentheses
-12x-36+16x-12=+3x-18+14
We move all terms containing x to the left and all other terms to the right.
-12x+16x-3x=-18+14+36+12
We simplify left and right side of the equation.
+1x=+44
We divide both sides of the equation by 1 to get x.
x=44
| 16=4w+9 | | -11+5n=-91 | | 5(-7b-7)= | | X-10=2x+4 | | d-14.25=23.5 | | 8+3b=-1+3(3+b) | | 3/4-1+1/2x=3/8x+1/4 | | 2x-3+x=3x+1 | | -3(x-1)=2x+48 | | 5(x-7)+x=6(x-7)+7 | | x^2-16x=.35 | | 5(x-1)2x=2x-5 | | -7y+26=-3(y-6) | | X+11+x+14=17 | | 6n-3n+3120=5400 | | 8(-5b+7)+4b= | | 1250=50+30x | | p-49=5(p+3) | | -30-5n=-6(n+4) | | -135/-9=15 | | 10(s-6)=-149 | | 8x+11+3=23-7x+4 | | 5(v-3)=-9v-29 | | 44c+49=457c-7 | | 8(X-1)=-2x+52 | | 9(x+1.4)=18 | | -3(6x-8)+7=-18+31 | | 2(x+7)+6=2x+2 | | 7x=5(2x-5) | | 12(r-5)=60 | | -4-4p=24 | | 3x+1-1=3x+2 |